ANALISIS KESIAPSIAGAAN, RESPONS, DAN PEMULIHAN DALAM PENANGANAN KASUS CORONA VIRUS DISEASE-19 (COVID-19) - Nursuciyati; Laksono Trisnantoro; Puti Aulia Rahma (Journal of Health Service Management, 2020)
Background: The number of global COVIF-19 cases was 191,148,056 million confirmed cases, 4,109,303 cases died, 204countries were infected, and 151 countries experienced local transmission. The outbreak of CoronaVirus Disease-19 (COVIF-19) inIndonesia is increasing. To date, 3,033,339 confirmed cases and 79,032 cases died. This situation causes COVID-19 cases to be stillthe main agenda in handling health in Indonesia and even globally.Objective: This study aims to identify and explain the analysis of preparedness, response, and recovery activities in handling Covid-19 cases in the Bima Regency.Methods: This type of research is qualitative research using a descriptive analysis approach that will describe an event based on theresults that have been analyzed. The research subjects were eight stakeholders who handled Covid-19 in Bima Regency. Researchdata will be collected using a checklist sheet from 2020 WHO guidelines.Data analysis is carried out using the Miles and Huberman model, namely: data collection, data reduction, data descriptionpresentation, conclusions.Results: Based on the percentage of activities that only developed by 21.43%, the preparedness and readiness phase, it canbe concluded that the handling of Covid-19 by stakeholders is not optimal due to several internal factors as well as from the community.Stakeholders have not conducted training and education for health workers regarding the handling of Covid-19 because no budgetplanning has been carried out. This has resulted in many health workers being exposed to Covid-19 in referral hospitals. Meanwhile,recovery by vaccinating the community is facilitated by all the primary health care in all areas of Bima Regency.Conclusion: In general, the Covid-19 Task Force in Bima Regency has not optimally carried out handling based on preparedness, response, and recovery aspects. The condition of handling Covid-19 cases has obstacles, namely the lack of health infrastructure, for example, health logistics and lack of public awareness in handling Covid-19 cases.